Utilization of welfare technologies, perceived importance, future plans and information needs: cross-sectional study to welfare, social and healthcare organizations in South Ostrobothnia - Hoffrén-Mikkola, Merja (Finnish Journal of eHealth and eWelfare, 2024)
The utilization of welfare technologies is considered important in social and health services to improve the quality and cost-effectiveness of care. Experiences from the Nordic countries show, however, that there are difficulties in the large-scale introduction of technologies and that the spread of technologies is slow. The purpose of this study was to investigate the effects of employee status, organizational form, and organization size on the use of welfare technologies in the health and wellness sector organizations operating in South Ostrobothnia. In addition, the purpose was to study the effects of employee status, organizational form, organization size and use of welfare technologies on the perceived importance of welfare technologies, plans to adopt new technologies and need for information about welfare technologies. The study was carried out as a cross-sectional quantitative e-mail survey. 121 people answered the survey. 45 % of them used welfare technologies at work. Managers or entrepreneurs, large organizations and those who used welfare technologies in their work considered the utilization of welfare technologies to be more important in their services than others and estimated that the organization will adopt more welfare technologies in the near future. The most needed information was about the characteristics of welfare technologies. In addition, those who already used welfare technologies needed knowledge also about the effects and effectiveness of welfare technologies, as well as about cost-effectiveness. To improve the utilization and perceived importance of welfare technologies in the health and wellness sector, trials and piloting of welfare technologies are important. In addition, the employees should have the opportunity to participate in the decision process of welfare technologies. Organizations should be supported with knowledge about the characteristics, effects, and impacts of welfare technologies, as well as about the cost effectiveness.